Measurement and Analysis in Transforming Healthcare Delivery : Volume 2: Practical Applications to Engage and Align Providers and Consumers - Sax, Harry C. (Springer International Publishing : Imprint: Springer, 2017)
This volume is complementary to Volume 1: Quantitative Approaches in Health Systems Engineering which provides in-depth analysis of the statistical and quantitative aspects of Health Systems Engineering. Volume 2: Practical Applications to Engage and Align Providers and Consumers builds upon these concepts with the integration of additional economic, performance and quality measures. Stressing the importance of changes in the economics of health care financing, it will serve as a resource for not only leaders of organizations, but also providers who will be practicing a different type of medicine from that of which they were trained. After defining the challenges, the authors will quantify and define funds flows and various margins necessary for viability, how providers will be measured and rewarded for quality, and the importance of accurate dashboard of physician performance. Types of payment systems, including capitation, ACOs, risk contracts, and hybrid forms of fee for service will be defined and their relative advantages discussed. Lessons from other countries that provide high quality care at a lower cost will be examined for applicability to our challenges. Finally, experts in leadership will focus on influencing behavior to achieve results while remembering that healthcare is about the patient. This textbook will serve as a useful resource for clinicians, healthcare executives, governmental agencies, and emerging leaders in organizations.
Keywords: Medicine.; Health administration.; elektronické knihy; electronic books